Novel organic-inorganic silica based sol-gel hybrid materials for sorptive extractions of organophosphorus pesticides - Krishna Veni Veloo, 1985-; Wan Aini Wan Ibrahim, supervisor; Mohd. Marsin Sanagi, supervisor; Fakulti Sains (2012)
Thesis (Ph.D (Kimia)) - Universiti Teknologi Malaysia, 2012